2021
DOI: 10.1371/journal.pone.0252956
|View full text |Cite
|
Sign up to set email alerts
|

Performing arts as a health resource? An umbrella review of the health impacts of music and dance participation

Abstract: An increasing body of evidence notes the health benefits of arts engagement and participation. However, specific health effects and optimal modes and ‘doses’ of arts participation remain unclear, limiting evidence-based recommendations and prescriptions. The performing arts are the most popular form of arts participation, presenting substantial scope for established interest to be leveraged into positive health outcomes. Results of a three-component umbrella review (PROSPERO ID #: CRD42020191991) of relevant s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…In addressing these questions, present evidence remains limited. For instance, the recent review cited above found that as little as 30 min of music-making was associated with positive health effects in healthy populations, but could not support any further conclusions regarding the optimum music-making type, duration, frequency and health applications (McCrary et al, 2021). Such a detailed understanding is needed to inform evidence-based policy, prescriptions and care (Bickerdike et al, 2017;Clift et al, 2021), but is presently limited by common features of a young and developing evidence base: a substantial heterogeneity of interventions and outcome measures (Fancourt and Finn, 2020;McCrary et al, 2021) elucidating a glut of potential mechanisms (Fancourt et al, 2021) and leading to disparate and often contradictory outcomes (Clift, 2020;Fancourt and Finn, 2020;McCrary et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In addressing these questions, present evidence remains limited. For instance, the recent review cited above found that as little as 30 min of music-making was associated with positive health effects in healthy populations, but could not support any further conclusions regarding the optimum music-making type, duration, frequency and health applications (McCrary et al, 2021). Such a detailed understanding is needed to inform evidence-based policy, prescriptions and care (Bickerdike et al, 2017;Clift et al, 2021), but is presently limited by common features of a young and developing evidence base: a substantial heterogeneity of interventions and outcome measures (Fancourt and Finn, 2020;McCrary et al, 2021) elucidating a glut of potential mechanisms (Fancourt et al, 2021) and leading to disparate and often contradictory outcomes (Clift, 2020;Fancourt and Finn, 2020;McCrary et al, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…FITT criteria have enabled broad research insights to be efficiently organized toward the establishment of a dose-response relationship between increased weekly aerobic physical activity (Intensity * Timing * Frequency) and improved health and reduced disease risk (Barisic et al, 2011;Arem et al, 2015;Rhodes et al, 2017 Similar links between acute music-induced autonomic changes and sustained modulations of autonomic tone are likely (Figure 1). However, studies of the effects of repeated music engagement on autonomic tone have only considered and prescribed FTT (Frequency, Timing, and Type) criteria (Takahashi and Matsushita, 2006;Le Roux et al, 2007;Okada et al, 2009;Chuang et al, 2011;Chlan et al, 2013;Hu et al, 2015;Helsing et al, 2016;Kunikullaya et al, 2016;Finn and Fancourt, 2018;Ribeiro et al, 2018;Fancourt and Finn, 2020;Mojtabavi et al, 2020;McCrary et al, 2021). Similarly, observational and intervention studies of the effects of repeated music engagement on health conditions linked to autonomic tone have not assessed and/or controlled the acute autonomic responses to music-making or listening (Fancourt and Finn, 2020;McCrary et al, 2021).…”
Section: The Physical Activity Roadmap-understanding Links Between Acute and Longer-term Autonomic Effectsmentioning
confidence: 99%
See 3 more Smart Citations